Cytotoxic effect of polyvinyl alcohol-magnetite composite - Baca Ramos, Karla (2023)
Polymeric hydrogel is a promising candidate for drug delivery applications due to its ability to encapsulate and release drugs. Incorporating magnetic particles enables controlled and specific release, providing sustained and targeted delivery. This study aimed to assess the cytotoxicity of the magnetite-polyvinyl alcohol (MPVA) hydrogel, specifically its magnetite content, using 3T3 fibroblast cells. The findings indicate that the MPVA hydrogel with magnetite nanoparticles was compatible with the cells and did not induce cell death. Incorporating magnetite nanoparticles into the PVA hydrogel improved its thermal stability and degradation temperature, disrupting the chain order, decreasing melting behavior, and fractional crystallinity of the hydrogel. The MPVA hydrogel demonstrated a higher gel fraction and crosslink density compared to the PVA hydrogel due to the presence of magnetite nanoparticles. The interaction between PVA and magnetite nanoparticles occurred through non-covalent forces, allowing for reversible interactions and dispersion of the nanoparticles within the PVA matrix. Although the cytotoxicity of the MPVA gel was similar to that of the PVA gel, the viability of fibroblast cells within the MPVA gel varied depending on the concentration. The MPVA hydrogel exhibited stronger attachment and induced irregular changes on the cell surface compared to the PVA hydrogel. Furthermore, the MPVA gel displayed paramagnetic behavior and controllable magnetization, as demonstrated by the hysteresis loop. These magnetic properties make the MPVA gel suitable for potential biomedical applications, including drug delivery, tissue engineering, and magnetic resonance imaging (MRI) contrast agents.